(untitled) (Bangladesh Journal of Medical Science, 2026)
Background Controlled space closure is a biomechanically demanding phase of orthodontic treatment. Clear aligner attachments are increasingly used for esthetic extraction or diastema management, but their stress-transfer pattern relative to conventional brackets requires structured evaluation. Methods A three-dimensional finite element in vitro simulation was performed using a maxillary dentoalveolar model with first premolar extraction spaces. Two appliance systems were compared: clear aligner therapy with optimized verticalrectangular attachments and conventional pre-adjusted edgewise brackets with stainless-steel archwire. A distalizing/ retraction load equivalent to 150 g per side was applied for space closure. Von Mises stress, maximum principal stress, periodontal ligament stress, tooth displacement, rotation tendency, and appliance deformation were recorded. Results The bracket model produced higher mean periodontal ligament von Mises stress at the canine cervical region than the aligner-attachment model (0.184 ± 0.021 MPa vs 0.132 ± 0.018 MPa, p<0.001). The aligner model showed lower peak alveolar cortical stress (4.31 ± 0.44 MPa) compared with brackets (5.76 ± 0.61 MPa, p<0.001), but exhibited greater crown tipping tendency (0.118 ± 0.014 mm vs 0.086 ± 0.011 mm, p=0.002). Brackets demonstrated more efficient bodily translation, with a root/crown displacement ratio of 0.79 ± 0.06 compared with 0.61 ± 0.07 for aligner attachments (p<0.001). Conclusion Clear aligner attachments distributed stress more diffusely and reduced peak periodontal and cortical bone stresses, whereas conventional brackets provided superior root control during space closure. Attachment geometry and staging compensation remain essential when aligners are used for extraction-space closure. Bangladesh Journal of Medical Science Vol. 25. Supplementary Issue-2 (2026), Page : S269-S275